Identifying virtual care modality in electronic health record data - Annie E. Larson; Kurt C. Stange; John Heintzman; Yui Nishiike; Brenda M. McGrath; Melinda M. Davis; S. Marie Harvey (Wiley, 2024)
Abstract Background Virtual care increased dramatically during the COVID‐19 pandemic. The specific modality of virtual care (video, audio, eVisits, eConsults, and remote patient monitoring) has important implications for the accessibility and quality of care, but rates of use are relatively unknown. Methods for identifying virtual care modalities, especially in electronic health records (EHR) are inconsistent. This study (a) developed a method to identify virtual care modalities using EHR data and (b) described the distribution of these modalities over a 3‐year study period. Methods EHR data from 316 primary care safety net clinics throughout the study period (4/1/2020‐3/31/2023) were included. Visit type (in‐person vs virtual) by adults >18 years old were classified. Expert consultation informed the development of two algorithms to classify virtual care visit modalities; these algorithms prioritized different EHR data elements. We conducted descriptive analyses comparing algorithms and the frequency of virtual care modalities. Results Agreement between the algorithms was 96.5% for all visits and 89.3% for virtual care visits. The majority of disagreement between the algorithms was among encounters scheduled as audio‐only but billed as a video visit. Restricting to visits where the algorithms agreed on visit modality, there were 2‐fold more audio‐only than video visits. Conclusion Visit modality classification varies depending upon which data in the EHR are prioritized. Regardless of which algorithm is utilized, safety net clinics rely on audio‐only and video visits to provide care in virtual visits. Elimination of reimbursement for audio visits may exacerbate existing inequities in care for low‐income patients.